2018
DOI: 10.24953/turkjped.2018.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the basic life support knowledge among schoolteachers: A cross-sectional survey in Kayseri, Turkey

Abstract: Dursun A, Özsoylu S, Emeklioğlu B, Akyıldız BN. Evaluating the basic life support knowledge among schoolteachers: A cross-sectional survey in Kayseri, Turkey. Turk J Pediatr 2018; 60: 702-708.Children spend a significant proportion of their day in school when they are not with their families.Therefore they might experience medical emergency situations due to injuries, complications of chronic health conditions, or unexpected major illnesses that occur in school. In cases of emergencies, school teachers are exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
(18 reference statements)
1
4
0
Order By: Relevance
“…This indicates that most of the participants do not know exactly when to call the EMS for help. This finding agreed with another study carried out in Turkey by Dursun, et al [30], which observed almost the same result. Most teachers (n=330, 61%) did not correctly identify cardiac arrest.…”
Section: Discussionsupporting
confidence: 93%
“…This indicates that most of the participants do not know exactly when to call the EMS for help. This finding agreed with another study carried out in Turkey by Dursun, et al [30], which observed almost the same result. Most teachers (n=330, 61%) did not correctly identify cardiac arrest.…”
Section: Discussionsupporting
confidence: 93%
“…Alhejaili et al reported similar results; hence, the findings are comparable [ 14 ]. Internationally, a study in Turkey revealed a lack of knowledge and skills in BLS among teachers [ 15 ]. In addition, another study in Shanghai, China, had a similar result with striction on the urgent need to educate staff members regarding first aid practices [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is called "Bystander Resuscitation" in the literature (2). Considering that children spend most of their time away from their families at school, we can say that teachers play a critical role in emergency situations where BLS is required (3).…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted on the BLS knowledge of teachers in Turkey, it was found that only 33.1% of them received this training. 47.5% of those who did not receive BLS training said that they could apply BLS to the student if necessary (3). Of course, it is not clear how correctly and effectively teachers in this group who do not have BLS training can do the application.…”
Section: Introductionmentioning
confidence: 99%